AB0696 Measurement of arterial stiffness in a cross-section of SLE patients and relationship to treatment with intravenous methlyprednisolone – a pilot study. (23rd January 2014) - Gayed, M.; Amissah-Arthur, M.; Stewart, K.; Jennens, H.; Braude, S.; Gordon, C.
Abstract : Background: SLE is associated with high cardiovascular (CV) morbidity and mortality. Patients have increased exposure to traditional and lupus specific risk factors, which accelerate plaque formation. Recurrent disease flares may facilitate vascular damage and inflammation, decreasing arterial compliance and increasing arterial impulse that transmits across the artery. Arterial stiffness is a recognised surrogate marker for CV disease and enables assessment of preclinical disease. Objectives: In this pilot study, our aim was to determine if SLE patients have significantly different pulse wave velocity (PWV), augmentation index (AI) and augmentation pressure (AP) compared to healthy controls in a cross-sectional study and to assess risk factors and whether these abnormalities are altered by administration of iv methylprednisolone(ivMP) in patients with active SLE (new BILAG A/B). Methods: SLE patients were recruited from established lupus clinics and consented. Healthy volunteers were recruited as controls. Lupus disease activity was measured using classic BILAG index. PWV, AI and augmentation pressure were measured in SLE patients and healthy controls. In 5 patients with disease flares, arterial stiffness measurements were repeated at 12 weeks following treatment with ivMP. Data that was normally distributed was analysed by student's T test and for non parametric data, Mann Whitney U test was used. Results: There were 67 SLE patients with mean disease duration ±sd of 10±7.4 years. The average age in SLE patients was 46±13.1 Vs 42±10.9 years in 45 controls who were gender and age matched (t test, p value=0.65). Participants in both groups were 91% female. The patients had significantly increased PWV at baseline 8.7±4.8m/s vs 6.2±1.2m/s, (t test p<0.001) compared to controls. AP was significantly higher in SLE group (IQR), 10 (7.5-19) Vs 8.5 (5.4-13) (Mann Whitney analysis p=0.029). AI were also higher in SLE patients compared to the control group on t test 29.6±12.1% vs 25±10% (t test p=0.02). There was a reduction in PWV in patients with active disease (BILAG≥5) at 12 weeks post treatment with ivMP compared to baseline (7.6±1.3m/s vs 10.6±7.5m/s p0.29). Multivariate analysis demonstrated that age and systolic blood pressure had the strongest association with PWV, AP and AI (p<0.001) and BMI correlates with AP and AI, (p=0.02 and <0.01) respectively. Conclusions: There was a statistically significant difference in arterial stiffness between SLE patients denoting the presence of early cardiovascular disease compared to healthy controls. There was a trend to increased arterial stiffness measurements in patients with active disease (BILAG≥5) however this was not statistically significant in this small pilot study. Treating acute flares led to an improvement in AP, AI and BILAG scores, suggesting that aggressive treatment with immunosuppression may dampen inflammatory burden, slowing down progression of CVD. SLE patients had increased arterial stiffness, which was not fully explained by systolic blood pressure, BMI and age. This supports that SLE is an independent risk factor for cardiovascular disease, and further larger studies need to be done to elucidate the mechanism. Disclosure of Interest: None Declared